Narratives about the macroeconomy - Peter Andre; Ingar Haaland; Christopher Roth; Mirko Wiederholt; Johannes Wohlfart (Leibniz Institute for Financial Research SAFE, 2024)
We provide evidence on narratives about the macroeconomy-the stories people tell to explain macroeconomic phenomena-in the context of a historic surge in inflation. In surveys with more than 10,000 US households and 100 academic experts, we measure economic narratives in open-ended survey responses and represent them as Directed Acyclic Graphs. Households' narratives are strongly heterogeneous, coarser than experts' narratives, focus more on the supply side than on the demand side, and often feature politically loaded explanations. Households' narratives matter for their inflation expectation formation, which we demonstrate with descriptive survey data and a series of experiments. Informed by these findings, we incorporate narratives into an otherwise conventional New Keynesian model and demonstrate their importance for aggregate outcomes.
Keywords: D83; D84; E31; E52; E71; 330; Narratives; Expectation Formation; Causal Reasoning; Inflation